Production of Calcium-Ammonium-Phosphate (CAP) Multinutrient Fertilizer from Acetylene Gas Industry Waste and Phosphoric Acid - Saudhia Aulizya Niswatul Khusna; Tri Andini Agustin; Ketut Sumada (G-Tech: Jurnal Teknologi Terapan, 2025)
The increasing global demand for food has raised the need for effective fertilizers, while the depletion of conventional raw materials and industrial waste accumulation have become pressing issues. Acetylene gas industries generate large amounts of semi-solid lime waste containing calcium hydroxide, which is often disposed of without treatment, causing environmental problems. This study aims to utilize acetylene waste as a raw material for producing Calcium-Ammonium-Phosphate (CAP) multinutrient fertilizer through a precipitation method using phosphoric acid (H3PO4) and ammonium hydroxide (NH4OH). The variables investigated include pH values (6,7,8,9,10) and waste mass (30,35,40,45,50 g). The resulting products were analyzed using Scanning Electron Microscopy–Energy Dispersive X-ray (SEM-EDX). The results indicate that the optimum pH to obtain the highest nutrient content of calcium (Ca), phosphorus (P), and nitrogen (N) is pH 10. In addition, variations in the mass of acetylene industry solid waste were found the optimum condition was achieved at 30 g of waste, which provided the highest concentrations of calcium, phosphorus, and nitrogen. This research demonstrates the potential of acetylene industry waste as an alternative raw material for sustainable fertilizer production.